Hand-to-mouth banks: Deposit inflows and the marginal propensity to lend - Felix Corell (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2025)
In modern macroeconomics, the marginal propensity to consume out of transitory income shocks is a central object of interest. This paper empirically explores a parallel concept in banking: the marginal propensity to lend out of unsolicited deposit inflows (MPLD). Using county-level dividend payouts as an instrument for deposit inflows, I estimate the MPLD for U.S. banks and show that before QE, the average bank operated "hand-to-mouth" - it transformed approximately every dollar of deposit inflow into new loans, consistent with tight liquidity constraints. However, since then, the MPLD has dropped to 0.35. Moreover, the MPLD decreases in banks' cash-to-asset ratio and deposit market power. The findings suggest that the QE-induced abundant reserves regime significantly relaxed liquidity constraints for the majority of banks, but did not eliminate them entirely.
Keywords: G21; E42; E51; 330; Banking; deposits; loans; money creation; reserves